2020
DOI: 10.1111/jvs.12956
|View full text |Cite
|
Sign up to set email alerts
|

Grazing livestock increases both vegetation and seed bank diversity in remnant and restored grasslands

Abstract: Questions Restoring grasslands is of great importance to biodiversity conservation to counteract widespread, ongoing losses of plant species diversity. Using source populations in remnant habitats and increasing functional connectivity mediated by grazing animals within and between habitats can benefit grassland restoration efforts. Here we investigate how grazing contributes to vegetation and seed bank diversity and composition in remnant and restored grassland communities in fragmented landscapes. Location S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…They may then gain dominance in the community and outcompete stress‐tolerant, low‐statured and slow‐growing grassland specialists as their rapidly extending herbaceous canopy deprives these specialists of light (Duprè & Diekmann, 2001; Hautier et al, 2009; Ceulemans et al, 2011; Auffret et al, 2017a). The continued grazing management of semi‐natural grasslands, on the other hand, keeps elevated P‐induced biomass production in check (Duprè & Diekmann, 2001), and maintains grassland habitat heterogeneity (Dirzo et al, 2014), crucial for the establishment and persistence of grassland specialists (Figure 4; Bullock et al, 1994; Kapás et al, 2020). Management may thus maintain high grassland species richness despite P eutrophication.…”
Section: Discussionmentioning
confidence: 99%
“…They may then gain dominance in the community and outcompete stress‐tolerant, low‐statured and slow‐growing grassland specialists as their rapidly extending herbaceous canopy deprives these specialists of light (Duprè & Diekmann, 2001; Hautier et al, 2009; Ceulemans et al, 2011; Auffret et al, 2017a). The continued grazing management of semi‐natural grasslands, on the other hand, keeps elevated P‐induced biomass production in check (Duprè & Diekmann, 2001), and maintains grassland habitat heterogeneity (Dirzo et al, 2014), crucial for the establishment and persistence of grassland specialists (Figure 4; Bullock et al, 1994; Kapás et al, 2020). Management may thus maintain high grassland species richness despite P eutrophication.…”
Section: Discussionmentioning
confidence: 99%
“…A proper grazing regime directly maintains the habitat by hampering both an increase in sward height and litter accumulation and favours habitat characteristic diversity (Riesch et al, 2020), with opposite effects on derived diversity. Grazing livestock was also found to have positive effects on the semi‐natural grassland seed bank, thus countering local extinction processes in the mid‐term (Kapás et al, 2020). Our models suggest a number of livestock units very similar to those indicated in the rural development programmes for the studied regions (0.3–1.2 livestock units per hectare) to obtain grassland biodiversity‐related subsidies.…”
Section: Discussionmentioning
confidence: 99%
“…Török and Helm, 2017, and citation therein). While Lipoma et al (2020, this issue) found that land‐use intensification decreased the role of biodiversity reservoirs (seed and bud banks) in resilience processes of the resident vegetation, Kapás et al (2020, this issue) showed that grazing livestock play a key role in facilitating both spatial and temporal dispersal in fragmented grasslands. Functional connectivity provided by grazing management also increases the possibility for species establishment from the propagule bank and the establishment of dispersed propagules from the surrounding landscape.…”
Section: Dispersal In Timementioning
confidence: 99%